2005
DOI: 10.1038/sj.ejcn.1602208
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient dilution associated with added sugar intake in elderly black South African women

Abstract: Objectives: To investigate the association between added sugar and macronutrient and micronutrient intakes, and to assess whether added sugar intake is related to biochemical indices of nutritional status, Mini-Nutritional Assessment (MNA) score, body mass index (BMI) and performance on physical function tests. Design: A cross-sectional, analytical study. Setting and subjects: Convenient sample of 285 institutionalised and community-dwelling black South African men and women aged 60 þ y. Methods: An interviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
52
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(61 citation statements)
references
References 19 publications
8
52
1
Order By: Relevance
“…[3][4][5] However, from the systematic reviews of Gibson 8 and Rennie and Livingstone 30 on the results of both observational and intervention studies, it appeared that the results were not necessarily linear or consistent across nutrients, populations and age groups; that quantification was hampered by differences in cut-offs to define categories of added sugar intake, ways of expressing sugar intake and methods of analyses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5] However, from the systematic reviews of Gibson 8 and Rennie and Livingstone 30 on the results of both observational and intervention studies, it appeared that the results were not necessarily linear or consistent across nutrients, populations and age groups; that quantification was hampered by differences in cut-offs to define categories of added sugar intake, ways of expressing sugar intake and methods of analyses.…”
Section: Discussionmentioning
confidence: 99%
“…These results concur with other studies that have investigated absolute intakes. [3][4][5] However, reported total energy intake is an important indicator of micronutrient intake, and in general, is significantly positively associated with micronutrient intakes. 24 Using the second approach to determine the dilution effect of added sugar (micronutrient intake per 4.18 MJ), a slight but significant nutrient dilution was found for thiamine, riboflavin, niacin, vitamin B 6 , magnesium, phosphorus and zinc in the men who consumed the most added sugar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of those investigating adults and elderly individuals, a study by Charlton et al 19 evaluating the diet of 285 African elderly individuals using a 24-hour food recall is noteworthy. These authors reported that the added sugar contribution to EI was 9.3% among men and 9.9% among women, which corroborates the findings in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in children, adolescents and adults have reported that a high energy percentage of the diet as free sugars is associated with lower intakes of various micronutrients (Alexy et al, 2003;Charlton et al, 2005;Kranz et al, 2005). In addition, a high free-sugar content of the diet has been associated with lower intakes of fiber (Kranz et al, 2005) and fruit and vegetables (Charlton et al, 2005). Regular consumption of foods high in free sugars does not have to be associated with micronutrient deficiencies (Ruxton, 2003).…”
Section: Free Sugarsmentioning
confidence: 99%